Decoding Lost Languages: A Philological Study of Ancient Texts - Nur Rahmi, Sri; Sok, Vann; Dara, Sokha (Journal of Humanities Research Sustainability, 2024)
Background. This research focuses on the decoding of ancient languages and the complexity of the symbols used by the Egyptian, Mesopotamian, and Indus Valley civilizations. The background of the research is based on the importance of understanding language as a key tool for uncovering the social, spiritual, and administrative lives of past civilizations. Purpose. The purpose of the study was to explain how these symbols can be interpreted using a combination of traditional philological methods and artificial intelligence technology.   Method. The methods used include manual linguistic analysis supported by modern algorithms to speed up the decoding process. Results. The results showed that the symbols of Ancient Egypt were easier to decrypt due to additional documentation, while the symbols from the Indus Valley remained difficult to understand. Symbols from Mesopotamia show complex dual meanings, especially in religious and astronomical contexts. Case studies show that ancient languages are multifunctional tools that reflect advanced social and spiritual structures.   Conclusion. The conclusion of the study confirms that an interdisciplinary approach is essential to uncover more secrets from past civilizations. This research enriches the understanding of ancient languages and shows that technology can speed up the decoding process, although it is not yet fully adequate. This contribution paves the way for further research involving global collaboration and the development of new technologies.